INVESTIGATION OF AERODYNAMIC PRESSURE DURING THE HIGH-SPEED TRAIN PASSAGE - Djabbarov, S. T. (Science and Transport Progress, 2016)
Purpose. The scientific paper highlights research of aerodynamic pressure and distribution of airflow velocity field along the moving high-speed train. Methodology. The study of velocity field distribution around the moving high-speed train is produced by simulating its movement as axially symmetric body with the ogive-shaped head and tail parts in compressible (acoustic) environment. Findings. The values of the absolute velocity (theoretical) of air flow generated by the body movement is determined (for the case when the body moves at a constant speed (200, 250, 350, 400 km / h) at a certain height from the ground), for the points located at different distances from the axis of the moving body (high-speed train). The calculations results allowed building the graphs of the air flow velocity in the acoustic environment along the moving body at different distances from it. Using the Bernoulli law (pressure change dependences on the flow velocity), the values of the overpressure generated by the air stream from the moving body were determined. Originality. This is the first theoretical study of the aerodynamics of the high-speed train as axially symmetric body with the ogive-shaped head and tail parts in compressible (acoustic) environment, moving with steady speed. The research results allow us to establish the distribution of the excess air flow pressure generated along the moving high-speed train. Practical value. The obtained results allows determining of the following parameters: 1) requirements for physical-mechanical and strength characteristics of the individual elements of the railway infrastructure in the areas of high-speed train movement, subject to aerodynamic pressure; 2) minimum distance from the track safe for people location during high-speed train passage.